2022
DOI: 10.1007/s10499-022-01035-x
|View full text |Cite
|
Sign up to set email alerts
|

Onion (Allium cepa) improves Nile tilapia (Oreochromis niloticus) resistance to saprolegniasis (Saprolegnia parasitica) and reduces immunosuppressive effects of cadmium

Abstract: The present study investigated the protective effects of dietary Allium cepa against Saprolegnia parasitica infections and the amelioration of cadmium-induced immunosuppression in Oreochromis niloticus. Saprolegnia isolates were recovered during an outbreak of saprolegniasis in farmed O. niloticus raised in a poor aquatic environment. Isolates were identified phenotypically as S. parasitica. Results were confirmed further by ITS gene sequencing. Four fish groups were kept in water with cadmium (1.5 mg/L) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 103 publications
(121 reference statements)
1
7
0
Order By: Relevance
“…In the current study, S. parasitica was pathogenic to Nile tilapia, leading to an 86.6% mortality rate. The clinical signs were similar to those reported in previous studies 38 42 . Elevated fish mortality might be attributed to the failure in the osmotic balance (hemodilution) and respiratory failure following massive destruction of the epidermis and degeneration of secondary lamella by invasive hyphal growth, histopathologically evidenced.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, S. parasitica was pathogenic to Nile tilapia, leading to an 86.6% mortality rate. The clinical signs were similar to those reported in previous studies 38 42 . Elevated fish mortality might be attributed to the failure in the osmotic balance (hemodilution) and respiratory failure following massive destruction of the epidermis and degeneration of secondary lamella by invasive hyphal growth, histopathologically evidenced.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Nile tilapia exposed to S. ferax zoospores (2 × 10 4 spore/L) showed cumulative mortalities of up to 92.5% over 3 weeks 47 . Stueland et al 38 revealed 89 and 31% cumulative mortalities when Atlantic salmons, Salmo salar L. S. declina zoospore (2.5 × 10 6 spore/mL) experimental infection in scaled carp fingerling revealed 55% cumulative mortalities 48 , S. parasitica spores at a concentration of 1.0 × 10 4 zoospores/L were able to induce 80% mortality ten days following challenges 42 , and Kumar et al 49 recorded 100% mortality in Pangasianodon hypophthalmus experimentally infected with S. parasitica zoospores (2 × 10 6 /L).…”
Section: Discussionmentioning
confidence: 99%
“…Cho and Lee (2012) obtained similar results for juvenile olive flounder (Paralychthys oilvaceus) when onion powder was supplemented at 0, 0.5, 1, 2, 3, and 5% into the trial diets. In literature, the positive effects of probiotics supplementation on the growth of cultured fish are well documented (Dimitroglou et al 2011;Merrifield et al 2010;Elgendy et al 2023). On the other hand, Akrami et al (2015) reported significantly higher weight gain and SGR for beluga (Huso huso) fed diet containing 1% onion powder.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial pathogens are considered one of the most significant problems hindering the expansion of the global aquaculture industry [1][2][3]. Motile aeromonads are Gramnegative, motile, facultatively anaerobic bacteria belonging to the family Aeromonadaceae [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, misuse of antibiotics may enhance the risk of occurrence and transmission of multidrug-resistant bacteria to humans and animals [4]. Terefore, it is crucial to develop innovative methods to control bacterial diseases in aquaculture, such as vaccination, immunostimulants, and nanomaterials [3,7].…”
Section: Introductionmentioning
confidence: 99%